Professional perspectives on fixed income portfolio management (Wiley-Academy, 2000)
In the turbulent marketplace of the New Economy, portfolio managers must expertly control risk for investors who demand better and better returns even from the safest investments. Finance and investing expert Frank Fabozzi leads a team of experts in the discussion of the key issues of fixed income portfolio management in the latest Perspectives title from his best-selling library. Perspectives on Fixed Income Portfolio Management covers topics on the frontiers of fixed income portfolio management with a focus on risk control, volatility framework for the corporate market, risk management for fixed income asset management, and credit derivatives in portfolio management. Other important topics include: attribution of portfolio performance relative to an index; quantitative analysis of fixed income portfolios; value-at-risk for fixed-income portfolios; methodological trade-offs. The book also provides a variety of illustrations